Hydration behaviour and infrared spectroscopy of pre-treatments effects on portland cement-eremospatha macrocarpa and laccosperma secundiflorum systems (2012)
"The effects of cold water extraction, incorptation of calcuim chloride (CaCl2) and aluminium sulphate (AL2(SO4)3) on the setting time (tmax), maximum hydration temperature (Tmax), time ratio(tR) and surface chemistry of Eremospatha macrocarpa and Laccosperma secundiflorum particles mixed with Portland cement was investigated. The mixtures were placed in thermally sealed thermos flasks for 24h after which tmax, Tmax and tR were measured. The tmax,Tmax and tR were 12.4 and 11.9h, 59.1 and 58.3oC, 1:1 and 1.1, respectively for untreated E.macrocarpa and L.secundiflorum and ranged from 5.2 to 10.7h, 57.7 to 83.7 oC and 0.5 to 0.9, respectively when treated with cold water and chemical addictives. Cold water extraction and chemical addictive significanlty improved the hydration parameters of rattan-cement system. CaCl2 performed better as a chemical accelarator than Al2(SO4)3 while L. secundiflorum inhibited cement setting more than E.macrocarpa. Infrared spectroscopy showed that incorporation of CaCl2 to L. secundiflorum particles helped expose cellulose to advance participation thereby enlarging its surface area for interpretation networking with cement. "